2016
DOI: 10.1016/j.fitote.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

ent-Kaurenoic acid-rich extract from Mikania glomerata: In vitro activity against bacteria responsible for dental caries

Abstract: Many studies have reported that medicinal plant extracts can inhibit oral pathogen growth or adhesion to surfaces and therefore reduce dental caries formation. The addition of these extracts to oral products like mouthwashes and dentifrices is considered an important strategy in caries control. In this sense, we have developed a Mikania glomerata extract with high ent-kaurenoic acid content (KAMg). So, this work describes the preparation of such extract and the development of a validated HPLC-DAD method to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
0
25
0
2
Order By: Relevance
“…Recent studies have shown that diterpenes are very effective in inhibiting different microorganisms, including oral pathogens. 44,57 The diterpene, phytol, although not abundant in B. campestris flower oil, may be an important contributor to the activity, since its role in antibacterial activity against oral microorganisms has already been described. 44,51 The EO of the B. campestris flower showed very strong to moderate activity against all the aerobic and anaerobic bacteria tested and could be a natural alternative in the prevention of diseases caused by oral microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that diterpenes are very effective in inhibiting different microorganisms, including oral pathogens. 44,57 The diterpene, phytol, although not abundant in B. campestris flower oil, may be an important contributor to the activity, since its role in antibacterial activity against oral microorganisms has already been described. 44,51 The EO of the B. campestris flower showed very strong to moderate activity against all the aerobic and anaerobic bacteria tested and could be a natural alternative in the prevention of diseases caused by oral microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…KAMg was prepared and characterized as described by Moreira et al (2016). The KA content in the extract was determined after the development and validation of a reverse-phase HPLC analytical method, which corresponded to about 48% of KA content in KAMg (Moreira et al 2016). The KA samples used in this work were obtained from the leaves of M. glomerata just as described by Soares et al (2019).…”
Section: Obtention Of the Ent-kaurenoic Acid-rich M Glomerata Extracmentioning
confidence: 99%
“…In a recent study, our research group described the entkaurenoic acid-rich extract from M. glomerata Sprengel (KAMg) as a new proposal of antimicrobial products for oral care. The results presented by the authors showed that KAMg was effective in inhibiting the formation of Streptococcus mutans biofilm (Moreira et al 2016). In view of the biological potential of this extract and its major component (ent-kaurenoic acid -KA - Figure 1), the present study was carried out to evaluate the cytotoxic potential of KAMg through the clonogenic efficiency assay and the genotoxic potential of KAMg and KA in the V79 (Chinese hamster lung fibroblasts) cell line through the cytokinesis-block micronucleus assay.…”
Section: Introductionmentioning
confidence: 98%
“…25,27 Briefly, the selected operational factors related to the chromatographic method were: mobile phase flow rate (Flow), column oven temperature (Temp. ), percentage of organic solvent in the mobile phase (B, in %), detection wavelength (λ), and volume of injected samples (Inj.).…”
Section: Robustnessmentioning
confidence: 99%